Chile : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report, 2018)
The Chilean economy is recovering from a prolonged slowdown that started with the decline in copper prices in 2011 and intensified over the past two years. The new administration, which took office in March, aims at reinvigorating investment and economic growth through structural reforms, but a divided Congress may constrain the reform space.